Case Report: Advantages of High-Resolution MRI in Evaluating the Efficacy of Drug Therapy for Intracranial Atherosclerotic Plaques - Zheng, Tao; Liu, Lei; Li, Li; Gao, Yang; Guo, Runcai; Zhou, Zhi; Liu, Zunjing; Liu, Kunpeng (Frontiers in Aging Neuroscience, 2022)
Intracranial atherosclerotic stenosis is one of the main causes of ischemic stroke and transient ischemic attack. High-resolution magnetic resonance imaging allows us to directly observe the intracranial artery wall, accurately assess the condition of the vascular wall, and quantitatively analyze the vascular wall and intracranial atherosclerotic plaque load. We report a case of acute cerebral infarction with left middle cerebral artery stenosis. During the first 3 weeks, the patient was treated with aspirin 100 mg and clopidogrel 75 mg daily. Afterwards, the patient continued to be given aspirin, and cilostazol 100 mg twice daily was given instead of clopidogrel. After 24 months of follow-up, we observed a significant reversal of intracranial atherosclerotic plaque using high-resolution MRI (HR-MRI) and discussed the advantages of HR-MRI in evaluating drug therapy for intracranial atherosclerotic plaque.